Cover Picture: Trap Inlaid Cationic Hybrid Composite Material for Efficient Segregation of Toxic Chemicals from Water (Angew. Chem. Int. Ed. 32/2022). Issue 32 (9th June 2022) - Fajal, Sahel; Mandal, Writakshi; Mollick, Samraj; More, Yogeshwer D.; Torris, Arun; Saurabh, Satyam; Shirolkar, Mandar M.; Ghosh, Sujit K.
Abstract : A unique anion exchangeable hybrid composite aerogel material was fabricated by Sujit K. Ghosh and co‐workers in their Research Article (e202203385 ) by strategically implanting a stable cationic metal–organic polyhedron in a hierarchically porous metal–organic gel material. The composite scavenger efficiently and selectively sequestrates various metal‐based toxic oxoanions from natural and simulated industrial wastewater samples in both batch and dynamic column exchange sorption experiments.